PENGARUH FOMO DAN HEDONIC MOTIVATION TERHADAP PENGGUNAAN PAYLATER (STUDI KASUS MAHASISWA DI KOTA MEDAN): Pengaruh FoMo Terhadap Penggunaan Paylater Pada Mahasiswa Di Kota Medan, Pengaruh Hedonic Motivation Terhadap Penggunaan Paylater Pada Mahasiswa Di Kota Medan, Pengaruh FoMo dan Hedonic Motivation Terhadap Penggunaan Paylater Pada Mahasiswa Kota Medan - Suci Afria Sasty Siregar; Miranda, Miranda; Dewi Anggita, Nadya; Lestari, Dini (Universitas Sumatera Barat, 2023)
This study aims to find out how big the hedonic lifestyle is in consumptive behavior in students of the This study aims to determine how much influence fomo, hedonic motivation has on the use of paylater on students in Medan City. This research is included in the type of quantitative research. The population in this study were students of Medan City. The samples in this study were students from UNIMED, UINSU, and UMSU. The sampling technique that can be used in this research is random sampling. Data analysis techniques used are data reduction, data presentation, and conclusions. The results of the research on the t test (partial) show that Fomo has a significant value of 0.001 <0.05. Hedonic Motivation has a significant value of 0.587 > 0.05. The F test (simultaneous) has a significant value of 0.000 <0.05. The conclusion in this study is that H1 is accepted, which means that Fomo has an influence on the use of Paylater, H2 is rejected, which means that Hedonic Motivation has no effect on the use of Paylater, and finally H3 is accepted, meaning that Fomo and Hedonic Motivation have an effect simultaneously on the use of Paylater by students in Medan City. especially at UNIMED, UINSU, and UMSU.